2010
DOI: 10.1074/jbc.m110.183723
|View full text |Cite
|
Sign up to set email alerts
|

A Noncompetitive Small Molecule Inhibitor of Estrogen-regulated Gene Expression and Breast Cancer Cell Growth That Enhances Proteasome-dependent Degradation of Estrogen Receptor α

Abstract: The mechanisms responsible for 17␤-estradiol (E 2 )-stimulated breast cancer growth and development of resistance to tamoxifen and other estrogen receptor ␣ (ER␣) antagonists are not fully understood. We describe a new tool for dissecting ER␣ action in breast cancer, p-fluoro-4-(1,2,3,6,-tetrahydro-1,3-dimethyl-2-oxo-6-thionpurin-8-ylthio) (TPSF), a potent small-molecule inhibitor of estrogen receptor ␣ that does not compete with estrogen for binding to ER␣. TPSF noncompetitively inhibits estrogen-dependent ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 77 publications
1
26
0
Order By: Relevance
“…MCF-7 cells grown in medium containing E 2 formed large colonies. The addition of 10 M TPSF completely blocked formation of MCF-7 cell colonies (47). Thus, TPSF inhibits estrogen stimulation of both anchorage-dependent and anchorage-independent growth of breast cancer cells.…”
Section: Down-regulation Of Er␣ Levels By a Small Molecule Inhibitormentioning
confidence: 90%
See 2 more Smart Citations
“…MCF-7 cells grown in medium containing E 2 formed large colonies. The addition of 10 M TPSF completely blocked formation of MCF-7 cell colonies (47). Thus, TPSF inhibits estrogen stimulation of both anchorage-dependent and anchorage-independent growth of breast cancer cells.…”
Section: Down-regulation Of Er␣ Levels By a Small Molecule Inhibitormentioning
confidence: 90%
“…Because TPSF has very little or no effect on the levels of AR and GR, TPSF is highly selective for down-regulation of ER. The proteasome inhibitor MG132 abolished down-regulation of ER␣ by TPSF (47). Thus, TPSF influences receptor levels at least in part due to its ability to enhance proteasome-dependent degradation of ER␣.…”
Section: Down-regulation Of Er␣ Levels By a Small Molecule Inhibitormentioning
confidence: 95%
See 1 more Smart Citation
“…21 Another interesting option is to use such assays for the identification and characterization of protein destabilizers (e.g., estrogen receptor antagonists). 22 Finally, our assays may be applied to identify or characterize pharmacological chaperones, which have been described to correct enzyme deficiencies. 23 Our results revealed that protein stability, which is a fundamental cellular mechanism, can be directly influenced by small-molecule ligands.…”
mentioning
confidence: 99%
“…Noncompetitive ERα inhibitors targeting this unmet therapeutic need, including DIBA, TPBM, TPSF, and LRH-1 inhibitors that reduce ERα levels, show limited specificity, require high concentrations (>5 μM), and usually have not advanced through preclinical development (9)(10)(11)(12). These noncompetitive ERα inhibitors and competitor antiestrogens are primarily cytostatic and act by preventing estrogen-ERα action; therefore, they are largely ineffective in therapy-resistant ERα containing cancer cells that no longer require estrogens and ERα for growth.…”
mentioning
confidence: 99%